Optimalisasi Pembelajaran Pendidikan Agama Islam Melalui Evaluasi Berbasis Proyek di SMPN 1 Kauman - Titin Riski Yana; Syifa Nur 'Afiah; Tiyas Nur Rohmawati; Tsabit Aqdaam Hikmawan; Ulwan Chasbi; Nurul Malikah (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
Islamic Religious Education (PAI) plays an important role in shaping the character and morals of students in Indonesia. Even though it has a strategic function, PAI learning often faces challenges, such as low student involvement and monotonous methods. To overcome this, project-based evaluation (Project Based Learning) is proposed as an innovative approach. This method emphasizes students' active involvement through exploration and collaboration in projects relevant to Islamic values. By implementing project-based evaluation, it is hoped that students will not only understand religious concepts theoretically but also be able to internalize and apply them in everyday life. This research aims to explore the implementation of project-based evaluation in PAI learning, as well as its impact on increasing student motivation, creativity and skills. Through this approach, PAI learning is expected to become more interesting and meaningful, in line with the demands of 21st century education